The business potential of Trigona Peunawa Samudra honey in the form of simple patent rights as an effort to develop university economic independence - Natsir, Muhammad; Ulya, Zaki; Sahara, Siti; Wilsa, Wilsa (Jurnal Geuthèë: Penelitian Multidisiplin, 2024)
Linot bees are a type of bee that produces quality honey and has health benefits. The Faculty of Law of Samudra University tried to develop linot bee cultivation in community service activities and involved students, with the hope that it would provide benefits for Samudra University to become an independent university. This honey was then named Trigona Peunawa Samudra. This activity aims to determine packaging that is suitable for sale and in preparation for registering a simple patent. So that it can be managed properly by Samudra University. The method used consists of 3 stages. These stages consist of the procurement stage, the packaging stage, and the honey product labeling stage. The implementation of the program began with coordination with the university to obtain land for linot beekeeping, and as an initial stage of licensing the activity was carried out. Furthermore, the implementation of socialization and debriefing of beekeeping that has been learned from professional beekeepers and the process of monitoring beekeeping so that it can be traded.